Study guides

☆☆

Q: What is 11x plus 8 equals 6x plus 43?

Write your answer...

Submit

Still have questions?

Related questions

If 6x + 10 = 11x , then x=2.

(4, 8)

5x + 32 = 11x - 105x - 11x = -10 - 32-6x = -42x = 7

6x + 5x = 11x

-5x+1 = 6x -5x-6x = -1 -11x = -1 x = 1/11

your equation is this... 2x3 + 11x = 6x 2x3 + 5x = 0 x(2x2 + 5) = 0 x = 0 and (5/2)i and -(5/2)i

you say: 5x+7=84-6x 5x+6x+7=84-6x+6x 11x+7=84 11x+7-7=84-7 11x=77 x=77/11 x=7

6x + 3 = -7 -5x 6x + 5x = -7 -3 11x = -10 x = -10/11

11x + 2y

11x-7

11x + 2

It is: 11x -2 simplified

(3x+1)(2x+4)

Fascinating ! Thanks for sharing.Would you like to know what value of 'x' makes that statement true ? You can find it like this:11x + 8 = 6x + 33Subtract 8 from each side:11x = 6x + 25Subtract 6x from each side:5x = 25Divide each side by 5:x = 5

11x+2y+9 is the final answer.

This expression can be simplified to: 2-6x

2x + 15 = 8x + 43 -6x = 28 x = -6 / 28 = -3 / 14

If you mean: 6x-4x-2+11x then it can be simplified to 13x-2

Assuming that the first operator is 6x^2. The factors are (6x-5)*(x-1)

-6x

6x+x = 7x

(9,6)

x/6 + x/5 = 11 Multiply throughout by 30: 5x + 6x = 330 => 11x = 330 => x = 30

6x plus 3 equals 8x plus 14 when solved mathematically is equal to x = -5.5.

6x